2019
DOI: 10.35774/econa2019.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Financial Instability on Exchange Risks of Port Sector Enterprises

Abstract: The increase of the degree of impact of financial risks on the results of operations and financial stability of the company is associated with a number of factors. They are the rapid volatility of the economic situation in the country and the financial market, the expansion of the sphere of financial relations of economic entities, the emergence of new financial technologies and tools, as well as a number of others factors. Therefore, the identification of the economic nature of financial risks and the establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most Chinese companies still need to incorporate financial risk management into their daily management, the corporate financial risk is not yet widely managed, which was put forward at the first insurance conference of the American Management Association [ 5 ]. Ilchuk and Shyshkina found that later, with the continuous development and improvement of risk management theory and practice, people began to gradually introduce these theories and practices into enterprise financial risk management [ 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most Chinese companies still need to incorporate financial risk management into their daily management, the corporate financial risk is not yet widely managed, which was put forward at the first insurance conference of the American Management Association [ 5 ]. Ilchuk and Shyshkina found that later, with the continuous development and improvement of risk management theory and practice, people began to gradually introduce these theories and practices into enterprise financial risk management [ 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%